PERANCANGAN CHECK DAM PRAMUKA UNTUK MENGATASI SEDIMENTASI DI BANJIR KANAL BARAT KOTA SEMARANG - Susilowati Susilowati; Langlang Adi Pratama; Dwi Kurniani; Suseno Darsono (Jurnal Karya Teknik Sipil, 2014)
West Flood Canal is one of the flood control infrastructure that was built to address the flooding problems in the city of Semarang. These functions must be kept in accordance with its function . Rehabilitation of the West Flood Canal has been done to increase the flow of flood carrying capacity is reduced due to sedimentation. This sedimentation caused by erosion upstream watershed Garang . Sediment Pengendalu banguna check dam should be built in the upper reaches of the river to control the tilt base. The purpose of this study is to design a sediment control structures in order to reduce sedimentation in the river downstream of the cause sedimentation, reducing the capacity of the West Flood Canal and causing flood water could not be contained anymore, causing flooding. As well as the presence of the check dam is expected to address the scouts scour at the bridge, so that the pillars of the bridge can be protected. Hydrology analysis to calculate the flood discharge using a HEC - HMS software with synthetic unit hydrograph of the SCS (Soil Conservation Service) in a 100 -year return period. 100 -year flood discharge in the location of 386.9 m3/second. Analysis of erosion using the USLE (Universal Soil Losses Equation) obtained the value erosion of 1.85 mm/yr ( 32.01 tonnes/ha/yr). From the analysis of erosion sedimentation values obtained with the formula of suripin (2004) amounted to 2,677 t/h/yr. Location check dam to be built at the downstream bridge Scout, Pudak Umbrella, Semarang. With the results obtained hydrological analysis was conducted with the physical planning of check dams as follows : lighthouse spillway crest elevation of +283.65 checkerboard with an effective height of 4 m and a depth of 2.2 m elevation foundation +277.45, the width of the main spillway mercu obtained dam 50 m wide, with discharge (Q) plans a return period of 100 years at 386.094 m3/dtk, high wing checkerboard of 3.45 m with a height of 0.8 m surveillance , checkerboard construction is masonry times , peak elevation +281.65 dam spillway sub summit with summit height of 2 m and a depth of 1.5 m foundation , sub- high-wing dams with a height of 2.9 m by 0.8 m surveillance, construction of a masonry dam sub times, with thickness of 1 m, the construction of a masonry protection floor is empty. Purpose of this is the construction of check dams to reduce the slope of the river so that the water velocity can be decreased and the river bed material transport capacity can be reduced, consequently the rate of sedimentation in the West Flood Canal can be reduced, thereby reducing the cost of routine dredging of sediment is reduced.